IMPROVEMENT OF PLANNING METHODOLOGIES OF AUDIT OF CREDIT AND DEBT TRANSACTIONS - Mo‘ydinov Ozodbek Olimjonovich (Web of Journals Publishing, 2026)
This article discusses the improvement of planning methods for auditing credit and debt operations at enterprises. Their content is developed from the set goal and specific tasks set for its implementation.
Keywords: Credit, audit, Planning, obligation, principle. Auditor, debt, debtor, financial period, tax.